Bifurcation points of nonlinear operators: existence theorems, asymptotics and application to the Vlasov-Maxwell system (2016)
Existence theorems about bifurcation points of solutions for nonlinear operator equation in Banach spaces are proved. The sucient conditions of bifurcation of solutions of boundary-value problem for Vlasov-Maxwell system are obtained. The analytical method of Lyapunov-Schmidt-Trenogon is employed.